Etnis Cina pada novel Di Kaki Bukit Cibalak karya Ahmad Tohari: representasi gagasan tentang keselarasan hidup - Prakoso, Teguh; Rusyana, Enang; Khasanah, Venus (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
The purpose this article is to obtain a representation of the idea of Chinese ethnic assimilation as a form of life harmony in the novel Di Kaki Bukit Cibalak (DKBC) based on the author's worldview. This article is qualitative research with descriptive analysis and a literary sociology approach based on Goldmann's genetic structuralism theory, Lotman's semiotics, and Mukařovskŷ backpack's literary aesthetics. In addition to finding the author's worldview, the text of DKBC is also seen as a dynamic aesthetic object. The primary data source is the novel DKBC by Ahmad Tohari; the secondary data source is articles and some reference literature related to diversity and harmonization. The stages of analysis were carried out using the first-level semiotic reading (heuristic) and continued with the second-level semiotic reading (hermeneutic). The results show an effort to build diversity and harmonization through blending, leading to life harmony. The emergence of Mulyani's perspective, which is different from her mother's in the novel DKBC, represents the complex and heterogeneous side of human life. The assimilation of ethnic Chinese is an important message about diversity and heterogeneity in Ahmad Tohari's novels. In such a context, the harmony of life represents ideas that the author voices well.